Effects of inspiratory muscle training on dyspnoea in severe COPD patients during pulmonary rehabilitation: controlled randomised trial. Issue 1 (25th January 2018) - Beaumont, Marc; Mialon, Philippe; Le Ber, Catherine; Le Mevel, Patricia; Péran, Loïc; Meurisse, Olivier; Morelot-Panzini, Capucine; Dion, Angelina; Couturaud, Francis
The benefit of inspiratory muscle training (IMT) combined with a pulmonary rehabilitation programme (PRP) is uncertain. We aimed to demonstrate that, in severe and very severe chronic obstructive pulmonary disease (COPD) patients, IMT performed during a PRP is associated with an improvement of dyspnoea. In a single-blind randomised controlled trial, 150 severe or very severe COPD patients were allocated to follow PRP+IMT versus PRP alone. The evaluations were performed at inclusion and after 4 weeks. The primary outcome was the change in dyspnoea using the Multidimensional Dyspnoea Profile questionnaire at the end of a 6-min walk test (6MWT) at 4 weeks. Secondary outcomes were changes in dyspnoea using the Borg (end of the 6MWT) and modified Medical Research Council scales and in functional parameters (maximal inspiratory pressure ( P Imax ), inspiratory capacity, 6MWT and quality of life). All analyses were performed on an intention-to-treat basis. Dyspnoea decreased significantly in both groups; however, the improvement of dyspnoea was not statistically different between the two groups. We only found a statistically significant greater increase of P Imax after IMT+PRP than after PRP alone. In this trial including severe or very severe COPD patients, we did not find a significant benefit of IMT during PRP+IMT as compared to PRP alone on dyspnoea, despite a significantly higher improvement of P Imax in the IMT group. Inspiratory muscle training during pulmonary rehabilitation has no additional effect on dyspnoea http://ow.ly/950d30ggYdd